2014
DOI: 10.17221/71/2013-jfs
|View full text |Cite
|
Sign up to set email alerts
|

Microsatellite DNA markers in Shorea platyclados (Dipterocarpaceae): genetic diversity, size homoplasy and mother trees

Abstract: ABSTRACT:Cross-specific amplification of microsatellite loci greatly enhances the effectiveness of this marker system. This shortcut would greatly enhance our examination of the gene flow and population structure of trees in diverse tropical rainforests. To explore the effectiveness and limitations of this approach, we examined allelic diversity at six microsatellite loci, originally developed in a congeneric species, in three populations of Shorea platyclados from Peninsular Malaysia. Fragment sizing was perf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 44 publications
(49 reference statements)
1
4
0
Order By: Relevance
“…Variations in fl anking regions and repeat numbers refl ect the occurrence of mutational processes in both the repeat and fl anking regions. Similar observations were made in Vitis (Masi et al 2004) and Shorea (Javed et al 2014) and insisting the requirement of information on underlying DNA sequence. However, with the availability of genome sequence of E. grandis, the primer sequence similarity search can be applied to fi nd the primer binding regions.…”
Section: /268supporting
confidence: 75%
See 1 more Smart Citation
“…Variations in fl anking regions and repeat numbers refl ect the occurrence of mutational processes in both the repeat and fl anking regions. Similar observations were made in Vitis (Masi et al 2004) and Shorea (Javed et al 2014) and insisting the requirement of information on underlying DNA sequence. However, with the availability of genome sequence of E. grandis, the primer sequence similarity search can be applied to fi nd the primer binding regions.…”
Section: /268supporting
confidence: 75%
“…Recently, it was emphasized that the sequence verifi cation of SSR alleles is critical for interpretation of the SSR polymorphism for genetic analysis (Barthe et al 2012). Further, size homoplasy is commonly reported among the SSR alleles (Curtu et al 2004, Javed et al 2014, hence, information on DNA sequence is essential before the utilization of SSR loci variations. Thus, in the present study, attempts were made to sequence the SSR-PCR amplicons generated in the inter-specifi c hybrid populations, E. tereticornis × E. camaldulensis and E. tereticornis × E. grandis.…”
Section: Introductionmentioning
confidence: 99%
“…Microsatellites [(SSRs) or short tandem repeats (STR)] are a commonly used marker system in plant genetics and breeding 42 . Chloroplastic microsatellites were widely used in population genetics of Dipterocarpaceae to assess genetic variation and population spatial structure at lower spatial and temporal scale 4749 , and the genetic diversity and gene flow with closely related species 50 . Our analyses of repeated regions, microsatellites, and the comparative plastomes analyses showed that a higher portion of the number and characteristics variations were found between species than between genera.…”
Section: Discussionmentioning
confidence: 99%
“…S2), homoplasy may be a serious problem when only fragment length analysis is performed, leading to underestimation of genetic variability and consequently to errors in population genetic inferences. Although the chance of homoplasy is proportional to the genetic distance between two individuals (Selkoe and Toonen, 2006), the few existing sequence-based studies revealed a high degree of fragment length homoplasy not only among different species but also within one species or a population (Estoup et al, 2002;Curtu et al, 2004;Anmarkrud et al, 2008;Javed et al, 2014;Germain-Aubrey et al, 2016). Our sequence analysis provide clear evidence of homoplasy at loci containing (1) SNPs or indels in FRs (5K23, Rub238h, Rub123a, 1G16, 1B06, 72H02 and Rub26a); ( 2) multiple repeat motifs (compound SSR; Rub47a, Rub238h, 1G16, Rub26a and Rub35a); and (3) interrupted (imperfect) repeats (mainly 5K23).…”
Section: Homoplasy Is a Common Phenomenonmentioning
confidence: 99%